2008
DOI: 10.1017/s1743921308028718
|View full text |Cite
|
Sign up to set email alerts
|

Properties of X-ray binaries in the Magellanic Clouds from RXTE and Chandra observations

Abstract: Abstract. The X-ray binary population of the SMC is very different from that of the Milky Way consisting, with one exception, entirely of transient pulsating Be/neutron star binaries. We have now been monitoring these SMC X-ray pulsars for over 10 years using the Rossi X-ray Timing Explorer with observations typically every week. The RXTE observations have been complemented with surveys made using the Chandra observatory. The RXTE observations are non-imaging but enable detailed studies of pulsing sources. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The temporal separation of these outbursts suggests an orbital period of P o ∼ (146 ± 2) d, however this needs further confirmation. We note that this orbital period is in agreement with the spin period, according to the Corbet relation (Corbet 1984;Laycock et al 2005;Corbet et al 2009). …”
Section: Periodicitiessupporting
confidence: 85%
“…The temporal separation of these outbursts suggests an orbital period of P o ∼ (146 ± 2) d, however this needs further confirmation. We note that this orbital period is in agreement with the spin period, according to the Corbet relation (Corbet 1984;Laycock et al 2005;Corbet et al 2009). …”
Section: Periodicitiessupporting
confidence: 85%
“…The Type I outbursts occur periodically at the time of the periastron passage of the neutron star, whereas Type II outbursts are much more extensive and occur when the circumstellar material expands to fill most, or all of the orbit. General reviews of such HMXB systems may be found in Reig (2011), Negueruela (1998), Corbet et al (2009) and Coe et al (2000Coe et al ( , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…However, we would expect to observe a giant burst for a long recurrence interval (type II, >10 37 erg s −1 ; Caballero et al 2008). On the other hand, if the orbital period for 1A 1118−615 is 17 yr, this binary system will have the longest orbital period than all the other known Be/XBPs shown by Corbet et al (2009).…”
Section: Discussionmentioning
confidence: 94%